Peningkatan Kemampuan Memahami, Mengaplikasi, dan Merefleksi melalui LKPD pada Materi Barisan dan Deret - DS, Hadi Kasmaja; Khotimah, Husnul; Talib, Ahmad (Jurnal PEKA (Pendidikan Matematika), 2026)
This classroom action research aimed to investigate the improvement of students’ abilities to understand, apply, and reflect through student worksheets (LKPD) on sequences and series at MA Shohibul Ilmi Bulukumba. The study was conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages, and was contextualized with local culture to enhance the meaningfulness of learning. The participants were 14 tenth-grade students. The research data consisted of process data and outcome data. Process data were obtained through observations of students’ learning activities and assessments of LKPD performance in the aspects of understanding, applying, and reflecting, which served as the basis for reflection and improvement in each cycle. Outcome data were collected through tests measuring students’ abilities to understand, apply, and reflect at the end of each cycle to determine their learning improvement. The results of Cycle I showed achievement levels of 60.71% for understanding, 61.61% for applying, and 58.93% for reflecting, while test mastery reached only 50%. After improvements were implemented in Cycle II, students' achievement increased by 22.62% to 83.33% in understanding, by 22.91% to 84.52% in applying, and by 32.32% to 81.25% in reflecting, with the test mastery level reaching 92.9%. These findings indicate that deep learning-based LKPD effectively improved students’ conceptual understanding, application skills, and reflective abilities in learning sequences and series.